Human Performance and Injury Prevention in Cold Weather Environments. Issue 4 (April 2022) - Bubnis, Matthew A.; Hulsopple, Chad
Abstract : A review of athletic performance in cold weather, including injury prevention, clothing, nutrition, and hydration recommendations. Abstract: This article serves as a primer for those practitioners who serve as subject matter experts in cold weather medicine, whether it be medical planning for an outdoor event, making the determination "it is too cold to exercise, " or investigating why an athlete is struggling to compete in a frigid environment. Cold weather exercise physiology is reviewed, and medical conditions that may impact performance at cold temperatures are briefly examined. Guidelines for cold weather risk assessment, injury prevention, and performance optimization also are discussed.